Trends in summer heatwaves in central Asia from 1917 to 2016: Association with large‐scale atmospheric circulation patterns. (3rd July 2019) - Yu, Shuang; Yan, Zhongwei; Freychet, Nicolas; Li, Zhen
Abstract: The changes in the frequency, duration, and intensity of summer heatwaves over central Asia during the period 1917–2016 were studied. On average, the frequency, duration, and intensity of heatwaves showed significant positive trends during the period 1917–2016, with enhanced rates during the last 50 years. During 1967–2016, the heatwave indices increased significantly in most of central Asia, especially in the western part. The number of heatwaves has increased by 1.3 times since the 1960s. Remarkable changes in the frequency and duration of heatwaves occurred during the 1990s in association with the inter‐decadal shift in the Silk Road pattern of atmospheric circulation around 1997. The results based on the ERA‐Interim reanalysis data set were well‐matched with the station observations during the period 1979–2016, whereas those based on the NCEP‐NCAR data set were less well matched. Heatwaves in central Asia were closely related to a zonal wave circulation pattern at 500 hPa with a centre of positive geopotential height anomalies over central Asia. This anomalous circulation pattern was rapidly enhanced during the 1990s, suggesting that large‐scale patterns of atmospheric circulation had a role in modulating the occurrence of heatwaves in central Asia. Abstract : The frequency, duration, and intensity of heatwaves in central Asia showed significant positive trends (e.g., heatwave numbers, 0.11 times∙decade −1 ) during the period 1917–2016, with enhanced rates during the last 50 years (e.g., heatwave numbers, 0.23 times∙decade −1 ). Remarkable changes occurred during the 1990s in association with the inter‐decadal shift in the Silk Road pattern of atmospheric circulation around 1997. The results based on the ERA‐Interim reanalysis data set were well‐matched with the station observations during the period 1979–2016.